The Effects of Different Wavelengths of Light on Tribolium castaneum - Pfannenstiel, Luke; Phillips, Thomas W. (My University, 2017)
Insects are known to be able to see different wavelengths of lights than humans can see. Because of this, there has been a lot of research done into using light to prevent damage caused by storedproduct pests. Common pests that research has been performed on are psocids (Diaz-Montano et al., 2015) and fruit flies (Saranwong et al., 2011). One of the biggest pests of stored-products is the red flour beetle Tribolium castaneum. Research on the attraction of different wavelengths of light has already been done on these beetles and published (Duehl et al., 2011), and my project mirrors that research. My hypothesis was that the shorter wavelengths of light would attract red flour beetles while the longer wavelengths of light would have no effect. My results show that, compared to a white light, the shorter wavelength light attracted more beetles. Compared to no light, there wasn’t a definite trend in wavelength of lights and attractiveness. The attractiveness of short-wavelength lights could be used to make traps for red flour beetles more effective and prevent damage to storedgrains.
Citation: Pfannenstiel, L. (2017). The Effects of Different Wavelengths of Light on Tribolium castaneum . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.